Big data management and the internet of things for improved health systems - Mishra, Brojo Kishore 1979-; Kumar, Raghvendra 1987- (IGI Global, 2018)
"This book explores a number of technologies can reduce overall costs for the prevention or management of chronic illnesses. These include devices that constantly monitor health indicators, devices that auto-administer therapies, or devices that track real-time health data when a patient self-administers a therapy. It also reviews mIoT and big data in healthcare fields"...Provided by publisher
Includes bibliographical references
Keywords: Data Mining; Medical Informatics; Telemedicine; Cloud Computing; Telemetry; Internet; Aufsatzsammlung